Caring for equality : a history of African American health and healthcare - McBride, David, 1949- (African American history series (Lanham, Md.), 2018)
African Americans today continue to suffer disproportionately from heart disease, diabetes, and other health problems. In Caring for Equality David McBride chronicles the struggle by African Americans and their white allies to improve poor black health conditions as well as inadequate medical care--caused by slavery, racism, and discrimination--since the arrival of African slaves in America. Black American health progress resulted from the steady influence of what David McBride calls the health equality ideal: the principle that health of black Americans could and should be equal to that of whites and other Americans. Including a timeline, selected primary sources, and an extensive bibliographic essay, McBride's book provides a superb starting point for students and readers who want to explore in greater depth this important and understudied topic in African American history.